Seroprevalence of Toxoplasma gondii Infection among Pregnant Women Admitted at Shahid Akbar Abadi Hospital, Tehran, Iran, 2010-2013 - Hadi Ghasemloo; Mohsen Ghomashlooyan; Hossein Hooshyar (Pasteur Institute of Iran, 2014)
Introduction : Toxoplasmosis, caused by Toxoplasma gondii, is a protozoan parasitic infection distributed worldwide. Early infection by this protozoa can lead to abortion and congenital toxoplasmosis in pregnant women. This study was conducted to determine the seroprevalence of T. gondii infection among pregnant women referring to Shahid Akbar Abadi Hospital, Tehran, Iran during 2010-2013. Methods: This descriptive study carried-out from October 2010 to March 2013. The blood samples from 785 pregnant women were collected and examined for specific IgG and IgM antibodies to T. gondii by ELISA method. Results: From 785 sera samples tested 541 (68.9%) were negative for any anti- T. gondii antibody. The women with anti- T. gondii positive and borderline IgG titers comprised 31.1% of the population study. T. gondii specific IgM was negative for all the pregnant women examined, and only for 6 women the titer showed to be at borderline. The rate of infection increased with age, as the highest rate of seropositivity (42.2%) was observed in 35-50 age group. However, no significant difference in the seroprevalence of T. gondii infection was observed between different age groups (P = 0.139). Conclusion: As a considerable number of the pregnant women were negative for T. gondii antibodies and are prone to acquisition of acute T. gondii infection over the course of pregnancy, primary prevention measures and serological monitoring of seronegative pregnant women are important for preventing congenital toxoplasmosis. J Med Microbiol Infec Dis, 2014, 1 (2): 4 pages.